The Development of Traditional Games Patok Lele towards Sport Science, Health and Education Learning at SDN 15 Sitiung Dharmasraya - Edo Putra Yoga; Maldin Ahmad Burhan; Dian Estu Prasetyo (The Future of Education Journal, 2022)
Study background back by lack of interest student in play game traditional So needed  game game traditional in PJOK learning for increase interest students Based on problem the so researcher develop game traditional peg catfish.Development using the research and development (R&D) Borg & gall model, model development borg & Gall has ten step. On step. On step study this is shared Becomes two stages, that is Step preliminary and Step development. Two stages that explained as following: 1) Potential and problem; 2) Data Collection; 3) Design product; 4) Validation product; 5) Revision usage; 6) Test try early; 7) Revision product. Whereas stage 8) Test try usage; 9 ) Revision product; 10) Production bulk no conducted in study because concerned with financing publishing products in the field mass.Results evaluation sheet validation game traditionally done by four validators generate the average value of 77% is categorized very valid. Test practicality by PJOK teacher with 100% percentage is categorized very practical and student with percentage 90% categorized very practical, while test 76% effectiveness categorized effective, based on results obtained so game traditional peg catfish in PJOK learning is categorized as valid, practical, and effective